Barriers to Implementation of Advanced Endoscopic Procedures - Gupta, Abhinav; Wlodarczyk, Jordan; Cologne, Kyle G. (Clinics in Colon and Rectal Surgery, 2023)
Advanced endoscopy has been shown to be useful in the diagnosis and treatment of both benign and low-grade malignant colorectal lesions. In fact, advanced endoscopic procedures are being adopted as standard approaches to these lesions in many places around the world; however, their implementation in the United States has not been as widespread. We ascribe the difficulty in implementation to two reasons: (1) lack of advanced endoscopic training and (2) failure in reimbursement models as they relate to endoscopy. In this article, we hope to describe these barriers and inspire colorectal surgeons to try and overcome them. As surgical specialists with a mastery of endoscopic techniques, colorectal surgeons would be able to maximize benefit for their patients and minimize health care costs in the long run.
Keywords: endoscopic surgery; reimbursement; training